Підкарпатська культура шнурової кераміки - Бунятян, К.П. (Археологія, 2010)
Здійснено аналіз концепцій підкарпатської культури, висунених у 1970-і рр. І.К. Свєшніковим та Я. Махніком, а також проблеми епішнурового горизонту пам’яток Верхньої Наддністрянщини і північно-західного Поділля. В настоящее время имеются две концепции подкарпатской культуры (ПК). Украинские исследователи ориентируются на построения И.К. Свешникова, зарубежные — Я. Махника. Исходя из существенных расхождений между ними, рассмотрено, какая концепция более соответствует развитию событий в северо-западном регионе Украины. Внешне концепция И.К. Свешникова (1974), выраженная коцентрировано в периодизации ПК, выглядит убедительно: для каждого ее этапа очерчено территорию, показано своеобразие вещевого комплекса, найдены аргументы для приблизительной датировки и т. д. Но в ней есть слабые звенья. Первое — это выделение начального этапа ПК. К нему исследователь отнес памятники с довольно оригинальным керамическим комплексом, которые сконцентрированы в Верхнем Поднестровье (так называемая группа Кавско-Колпец) и якобы предшествовали общеевропейскому горизонту КШК. Такая ранняя (до-КШК) позиция этих памятников не была подкреплена ни стратиграфическими наблюдениями, ни другими хоть в какой-то мере весомыми аргументами. Тем не менее, получалось, что этот регион выступал не только местом формирования ПК, но и одним из очагов возникновения КШК, поскольку именно с трансформацией этого начального комплекса исследователь связывал появление признаков второго этапа, в частности амфор, кубков и каменных топоров А-типов и иных, то есть собственно черт КШК. С другой стороны, погребения заключительного этапа ПК существенно отличались от предыдущего, особенно за сопровождающим инвентарем (цилиндрические кубки, черпаки, металлические изделия и др.). Таким образом, при спорности первого этапа и своеобразии третьего ПК как обладающая чертами КШК фактически сводилась к среднему периоду, памятники которого локализированы, главным образом, в Верхнем Поднестровье и едва заходят на северо-западное Подолье. Эти недостатки концепции И.К. Свешникова поправил польский археолог Я. Махник (1979), развивая ранее наработанные идеи. Ученый разделил памятники Верхнего Поднестровья на два горизонта — шнуровой и постшнуровой, таким образом отсекая от ПК памятники, отнесенные И.К. Свешниковым к позднему ее этапу. В развитии шнурового горизонта (то есть, собственно ПК) исследователь наметил три фазы, ориентируясь на общие закономерности эволюции КШК, подкрепленные здесь незначительным числом стратиграфических наблюдений. Группу Кавско-Колпец, которую И.К. Свешников рассматривал как исходную в формировании ПК, Я. Махник разместил на пограничье шнурового и постшнурового горизонтов. Верхним Поднестровьем этот исследователь собственно и ограничил КШК, отметив ее незначительное проникновение на Подолье в третьей фазе. Таким образом, ПК приобрела другое обличье, а вместе с тем четче проявились особенности регионов, на которые И.К. Свешников расширил это понятие. Пока в Верхнем Поднестровье развивалась ПК, на Подолье бытовала культура шаровидных амфор, потом их сменила постшнуровая культура. Что важно, характеризуя постшнуровой горизонт, Я. Махник обратил внимание на пестрость памятников, в которых сочетались черты предыдущей культуры (курганный обряд погребений, амфоры, возможное продолжение группы Кавско-Колпец) и новые образцы керамики (культуры Хлопице-Веселе и с чертами карпато-дунайских культур ранней бронзы), а также металлические вещи кавказского и карпато-дунайского происхождения. Иными словами, он показал смешанный синкретический характер этой культуры, особенно Подольского региона, где как бы пересекались старые традиции и новые, которые шли с запада (культура Хлопице-Веселе) и с юга (Карпато-Балканский регион). Тем не менее, это не помешало Я. Махнику в дальнейшем — при выработке последней концепции межано-вицкой культуры — включить оба региона (а также Западную Волынь — городокско-здолбицкую культуру) в эту культуру (Kadrow, Machnik 1997), перечеркнув тем самым собственные наблюдения. Этому, во-первых, противоречит погребальный обряд: в межановицкой культуре — грунтовые могильники, в Верхнем Поднестровье — курганные, на Подолье — курганные и в каменных гробницах либо соединяющие эти черты. Во-вторых, при наличии черпаков протомежановицкой фазы (2 экз.) и ранней (их больше, но они концентрируются в верховьях Днестра и Западного Буга) погребения этих регионов сопровождались в основном цилиндрическими кубками с ручкой или выступом, не характерными для межановицкой культуры, а также синкретическими образцами керамики или такими, которые тяготеют к Балкано-Карпатскому региону. К идее Я. Махника о влиянии карпато-балканских культур на Подольский регион обратились Н. Бандривский и Л. Крушельницкая (2005), предложив выделить здесь предкомаровскую группу памятников. Однако введение этого термина только вводит в заблуждение. Тезис авторов, что на смену культуре шаровидных амфор из-за Карпат на Подолию стали проникать носители другой культуры, проработан поверхностно, а предкомаров-ский горизонт, датированный 2750/2700—2000 гг. до Р. Х., синхронизирован с КШК (в частности, с краковско-сандомирской культурой) и в значительной степени с культурой шаровидных амфор, отличаясь от них только несколько большей продолжительностью. Расширенное понимание И.К. Свешниковым ПК (включение в нее постшнуровых памятников) отразилось на создании обобщающих работ по археологии Украины и непрочной ее позиции в системе других культур. К этому добавилась ориентация украинских исследователей на разные периодизационные схемы — центрально- или востосточноевропейскую. Но в любой системе относительная синхронность трех культур — ямной, шаровидных амфор и КШК — будет сохраняться, поскольку она засвидетельствована погребениями ямной культуры Северно-Западного Причерноморья, а также подтверждена радиокарбонными датами. Материал и дата поселения Сиде (Верхнее Поднестровье) свидетельствуют, что ПК сформировалась паралельно с КШК на территории Малопольши и шире. Однако через отсутствие пакета дат вопрос о ее продолжительности, как и хронологии постшнуровых памятников Украины, остается открытым. Today two conceptions of Pidcarpatska culture exist. Ukrainian scholars are oriented on the research made by J.K. Sveshnikov, while foreign ones — on the research made by G. Machnik. Based on significant differences between them, it is analysed which conception is more relevant to the events in the north-western region of Ukraine. Conception of I.K. Sveshnikov (1974), concentratively conveyed in the division into periods of Pidcarpatska culture, superficially looks convincing: each of its stage is determined territorially, peculiarities of materials are shown, arguments for approximate dating are found, etc. However, it has weak links. First of them is the determination of the initial stage of Pidcarpatska culture. The researcher referred to it sites with quite original ceramic complexes which concentrate in the Dnister River upper region (so-called Kavske-Kolpets group) and supposedly precede the common European horizon of Corded Ware culture. Such an early (pre-Corded Ware) position of these monumente was not supported neither with stratigraphic observations, nor with other arguments weighty at least to some extent. Nevertheless, this region derived to be not only a place of generation of Pidcarpatska culture, but also one of the centres of origin of Corded Ware culture, since the scholar related the advent of features of the second stage, particularly amphorae, bowls and A-type and other stone axes, in other words the very features of Corded Ware culture, with the transformation of this initial complex. On the other hand, burials of the final stage of Pidcarpatska culture significantly differed from the previous ones, especially with the supplementing inventory (cylindrical bowls, dippers, metalware, etc.). Consequently, with the disputable first stage and original third stage Pidkarpatska culture as the one having features of Corded Ware culture in fact came to the middle period, sites of which were localized mainly in the Dnister River upper region and hardly enter into the North-Western Podillya region. These defects of I.K. Sveshnikov’s conception were adjusted by Polish archaeologists J. Machnik (1979) who develop ed the ideas worked out earlier. The scholar divided the monuments of the Dnister River upper region into two horizons: Corded and post-Corded, having severed in that way from Pidkarpatska culture the sites referred by I.K. Sveshnikov to its late stage. In the development of Corded horizon (that is the very Pidcarpatska culture) the researcher outlined three phases coming from general patterns of evolution of Corded Ware culture, confirmed here by insignificant amount of stratigraphic observances. Kavsko-Kolpets group which was considered by I.K. Sveshnikov as an initial in generation of Pidkarpatska culture J. Machnik placed on the border between Corded and post-Corded horizons. This researcher confined Corded Ware culture within the Dnister River upper region, having noted its insignificant penetration into Podillya region at the third phase. In that way Pidkarpatska culture obtained other appearance, and at the same time peculiarities the regions, on which I.K. Sveshnikov extended this term, revealed themselves clearer. At the time when in the Dnister River upper region Pidcarpatska culture was developing, in Podillya region Globular Amphora culture prevailed, both were changed by «post-Corded culture». It is important that characterizing post-Corded horizon J. Machnik paid attention to the mixed character of monuments where features of previous culture (burials in barrows, amphorae, possible sequel of Kavsko-Kolpets group) and new ceramic examples (of culture Khlopitse-Vesele and with the traits of the Carpathian and Danube River region cultures of the Early Bronze Age), as well as metalware of Caucasus and the Carpathian and Danube region origin. In other words, he showed a mixed syncretic character of this culture, especially of Podillya region where old and new traditions coming from the West (Khlopitse-Vesele culture) and East (the Carpathian and Danube River region) as if intersected. Nevertheless, it did not prevent J. Machnik further, when he was developing recent conceprion of Mezhanovitska culture, from including both regions (as well as the Western Volyn region, Horodoksko-Zdovbytska culture) into this culture (Kadrow, Machnik 1997), which cancelled his own observations. It conflicts, first of all, with burial custom: burial grounds in Mezhanovytska culture, barrows in the Dnister River upper region, and barrows and stone tombs, or burials with both features in Podillya region. Secondly, with deepers of the proto-Mezhanovytska (2 items) and the Early phases (more items, but concentrated in the Dnister and Western Buh Rivers regions) the burials of these regions were supplemented mainly with cylindrical bowls with handles or juts not typical for Mezhanovytska culture, as well as with syncretic examples of ceramics or those close to the ones from Balcan and Carpathian region. N. Bandrivskyj and L. Krushelnytska (2005) took up the J. Machnik’s idea about influence of Carpathian and Balcan cultures upon Podillya region, and proposed to single out pre-Komarivska group of monuments here. However, introducing of this term deceives only. The authors’ thesis that Globular Amphora culture was changed by the people of another culture coming from behind the Carpathians to Podillya region is developed superficially, and the pre-Komarivskyi horizon dated from 2750/2700 to 2000 BC is synchronized with Corded Ware culture, particularly with Krak ow-Sandomierz culture, substantially with Globular Amphora culture, differing from them only with longer continuance. I.K. Sveshnikov’s widened understanding of Pidcarpatska culture which included post-Corded monuments there reflected in writing of generalizing works on archaeology of Ukraine where position of this culture is not firm in a system of other cultures. This situation is supplemented by the orientation of Ukrainian archaeologists towards different systems of division into periods: Central European and Eastern European. However, in any system relative synchronism of the three cultures (Yamna, Globular Amphora and Corded Ware ones) will remain because it is testified by the burials of Yamna culture of north-west coast of the Back Sea, and is supported by radiocarbon dating. Material and date of Side settlement in the Dnister River upper region shows that Pidcarpatska culture was forming simultaneously with Corded Ware culture on the territory of Lesser Poland and around. However, a problem of its duration, as well as of chronology of post-Corded sites of Ukrain, remains unsolved because of lack of a packet of dates.